2020
DOI: 10.1155/2020/4817239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Main Coronary Artery Using Optical Frequency Domain Imaging and Its Pitfalls

Abstract: Objectives. We aimed to assess the quality of optical frequency domain imaging (OFDI) of the left main (LM) arterial wall and describe and analyse potential artefacts in this setting. Background. OFDI is increasingly used to assess ambiguous lesions and optimize LM percutaneous coronary intervention. However, its ability to provide artefact-free high-quality images of coronary ostia and large segments such as the LM remains uncertain. Methods. We included 42 consecutive patients who underwent OFDI, including L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Notwithstanding the afore mentioned limitations, a recent study showed that LMCA was adequately assessed by OCT in more than 90% of the quadrants, most artefacts being located in the proximal segment [21]. The most commonly diseased LMCA segment is the bifurcation, where OCT imaging is accurate.…”
Section: Intracoronary Imaging In Lmca Diseasementioning
confidence: 99%
“…Notwithstanding the afore mentioned limitations, a recent study showed that LMCA was adequately assessed by OCT in more than 90% of the quadrants, most artefacts being located in the proximal segment [21]. The most commonly diseased LMCA segment is the bifurcation, where OCT imaging is accurate.…”
Section: Intracoronary Imaging In Lmca Diseasementioning
confidence: 99%
“…These experiences can affect a young person's self-perception that shapes a young person's image of themselves that can last a lifetime (Abramovitz 2005). Workers will witness more such experiences among the children they serve in a large-scale crisis, like a pandemic, as agencies face additional challenges and work demands increase (Roule 2020;Tavormina and Clossey 2015).…”
Section: Impact Of Covid-19 On Pcw Workersmentioning
confidence: 99%
“…The already limited resources to help children like Collin and their families are much scarcer during the pandemic, as PCW agencies are concerned with their very survival (Amandolare et al 2020;Roule 2020). Children need consistent, healthy relationships with adults who model proper behaviors (Abramovitz 2005;Madden and Aguiniga 2017).…”
Section: Additional Stressors On the Sector During The Pandemicmentioning
confidence: 99%
See 2 more Smart Citations